When Can Oil Economies Be Deemed Sustainable? - Luciani, Giacomo; Moerenhout, Tom (The Political Economy of the Middle East,, 2021)
This open access book questions the stereotype depicting all Gulf (GCC) economies as not sustainable, and starts a critical discussion of what these economies and polities should do to guarantee themselves a relatively stable future. Volatile international oil markets and the acceleration of the energy transition has challenged the notion that oil revenues are sufficient to sustain oil economies in the near to medium term. But what is the meaning of economic sustainability? The book discusses the multiple dimensions of the concept: economic diversification, continuing value of resources, taxation and fiscal development, labor market sustainability, sustainable income distribution, environmental sustainability, political order (democracy or authoritarianism) and sustainability, regional integration. The overarching message in this book is that we should move on from the simplistic branding of the Gulf economies as unsustainable and tackle the details of which adaptations they might need to undertake. Giacomo Luciani teaches at the Graduate Institute of International and Development Studies in Geneva, and at the Paris School of International Affairs, Sciences Po in Paris. His edited book The Rentier State (1987, with H. Beblawi), is frequently cited as reference for the concept. His latest edited book, Combining Economic and Political Development (2017), discusses economic policies to support democratic transitions and is available in open access. Tom Moerenhout teaches at Columbia University's School of International and Public Affairs and is a scholar at SIPA's Center on Global Energy Policy. He is involved as a practitioner on energy sector and structural reforms through his work as a consultant for the World Bank, International Institute for Sustainable Development and Bill & Melinda Gates Foundation, amongothers.